Sodium-based dry decarburization absorbent and preparation method thereof
By doping silica gel and other components in the alumina carrier, the sodium-based absorbents are solved, and the existing absorbents have limited absorption capacity, high regeneration energy consumption, poor high temperature stability and slow desorption rate during the carbon dioxide capture process, achieving a more efficient and economical carbon dioxide capture effect.
Patent Information
- Application Number
- CN202411805920.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
AI Technical Summary
During the carbon dioxide capture process, existing sodium-based absorbers have problems such as limited absorption capacity, high regeneration energy consumption, poor high temperature stability and slow desorption rate.
By doping silica carriers with sodium carbonate, trace potassium carbonate and trace magnesium chloride in the alumina carrier, traditional sodium-based absorbents are modified to improve their hygroscopicity, absorption efficiency and desorption rate, and enhance high temperature stability and low energy consumption regeneration capabilities.
The improved absorbent significantly improves the absorption efficiency and desorption rate of carbon dioxide, enhances high temperature stability, reduces regeneration energy consumption, and improves the efficiency and economicality of carbon dioxide capture.
Smart Images

Figure BDA0005179210030000071 
Figure BDA0005179210030000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental protection and energy, and specifically relates to a sodium-based dry decarbonization absorbent and a preparation method thereof. Background Art
[0002] Global climate change has become a key issue of concern to the international community. Carbon dioxide (CO2) is one of the main greenhouse gases, and its increased emissions have a significant impact on global temperature rise and climate variability. Therefore, reducing carbon dioxide emissions has become one of the key measures to address climate change.
[0003] Carbon dioxide capture and storage (CCS) technology is one of the important means to reduce CO2 emissions. This technology involves capturing carbon dioxide from industrial processes or energy utilization, and then transporting and storing it in underground geological structures to prevent it from entering the atmosphere. CCS technology can significantly reduce industrial emissions, especially CO2 emissions from power plants and heavy industries. In carbon dioxide capture technology, absorbent materials play a vital role. The absorbent separates CO2 from the gas mixture by physical or chemical means. Common absorbents include activated carbon, molecular sieves, metal organic frameworks (MOFs), and sodium-based and potassium-based alkali metal compounds.
[0004] At present, there are large differences in the decarbonation performance of absorption. The absorbent fixes CO2 in its structure through a chemical reaction with CO2. However, chemical absorbents often require high energy input during the regeneration process, and long-term use will cause the absorbent to deactivate. Existing absorbents have limited CO2 absorption capacity and reduced absorption efficiency in high temperature environments. Many absorbents reduce their selectivity for CO2 when absorbing other gases, and the regeneration process requires high energy consumption, which increases operating costs. Some absorbents are prone to deactivation during long-term use and have poor chemical stability, which limits their service life. In order to improve the performance of absorbents, researchers are constantly exploring and developing new absorbent materials or modifying existing materials. The goals of improvement include increasing absorption capacity, increasing desorption rate, reducing regeneration energy consumption, enhancing high temperature stability and improving selectivity.
[0005] Traditional sodium-based absorbents have become a widely used decarbonization material due to their strong absorption capacity and low cost. Traditional sodium-based absorbents have shown certain efficiency in the carbon dioxide capture process, but they also have the following shortcomings: (1) Limited absorption capacity: The CO2 absorption capacity of traditional sodium-based absorbents may not be sufficient to meet high-demand industrial applications. (2) High regeneration energy consumption: Sodium-based absorbents require higher energy input during the regeneration process, increasing operating costs. (3) Poor high-temperature stability: Under high temperature conditions, sodium-based absorbents may be deactivated, limiting their scope of application. (4) Slow desorption rate.
[0006] Therefore, it is of great significance to develop an improved sodium-based dry decarbonization absorbent. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide an improved sodium-based dry decarbonization absorbent in view of the deficiencies of the prior art, by modifying the traditional sodium-based absorbent by doping a silica gel carrier and sodium carbonate, a trace amount of potassium carbonate and a trace amount of magnesium chloride in an alumina carrier. This modification not only improves the hygroscopicity, absorption efficiency and desorption rate of the absorbent, but also enhances its stability under high temperature conditions and improves the low-energy regeneration capacity. Such technical improvements help to overcome the deficiencies in the prior art and improve the efficiency and economy of carbon dioxide capture.
[0008] In order to solve the above technical problems, the present invention discloses a sodium-based dry decarbonization absorbent, which is a silica gel-containing alumina loaded with sodium carbonate, potassium carbonate and magnesium chloride; wherein the absorbent comprises: by mass percentage, 5-8% silica gel, 10-30% sodium carbonate, 0.5-1% potassium carbonate and 0.3-0.5% magnesium chloride, and the rest is alumina.
[0009] Preferably, the absorbent comprises, by mass percentage, 6% silica gel, 30% sodium carbonate, 1% potassium carbonate and 0.4% magnesium chloride, with the remainder being aluminum oxide.
[0010] Wherein, the water vapor concentration of the absorbent during the absorption process is 0.02-0.04%.
[0011] The present invention also discloses a method for preparing a sodium-based dry decarbonization absorbent, which comprises the following specific steps:
[0012] S1. Pretreatment of alumina support;
[0013] S2. The pretreated alumina is impregnated in a silica gel solution, and the excess solution is removed, dried, and calcined to obtain an alumina carrier containing silica gel;
[0014] S3. The silica gel-containing alumina carrier is immersed once in a sodium carbonate solution, and after removing the excess solution, the silica gel-containing alumina carrier immersed once is immersed twice in a mixed solution of potassium carbonate and magnesium chloride, and after removing the excess solution, it is dried and calcined to obtain a sodium-based dry decarbonization absorbent.
[0015] Wherein, in S1, the pretreatment process is specifically: drying the alumina carrier at 100-150°C, and then calcining at 400-600°C for 3-5h.
[0016] Among them, in S2, the impregnation time in the impregnation process is 1 to 2 hours; the drying process conditions are drying at 80 to 120° C. for 6 to 12 hours; and the calcination process conditions are calcining at 400 to 800° C. for 2 to 4 hours.
[0017] Wherein, in S3, the immersion time in the one immersion process is 4 to 5 hours.
[0018] Among them, in S3, the impregnation time in the secondary impregnation process is 1 to 2 hours; the drying process conditions are drying at 80 to 120° C. for 6 to 12 hours; and the calcination process conditions are calcining at 200 to 400° C. for 2 to 4 hours.
[0019] Specifically, in some embodiments of the present invention, the absorption rate of the absorbent prepared by the present invention on a mixed gas with 15% carbon dioxide and the desorption rate after absorption saturation are tested in a constant temperature absorption device, thereby verifying the absorption-desorption performance of the absorbent, thereby demonstrating the application prospects of the absorbent provided by the present invention in the field of carbon dioxide capture and storage.
[0020] The advantages of the technical solution of the present invention are as follows:
[0021] 1) Synergistic effect of components
[0022] The absorbent combines sodium carbonate, potassium carbonate, silica gel, magnesium chloride and alumina carrier to exert the synergistic effect of multiple components. Sodium carbonate, as the main carbon dioxide absorbent, has a strong absorption capacity but a slow desorption rate. The introduction of 0.5-1% potassium carbonate not only improves the absorption rate of the absorbent, but also improves the moisture management ability of the material through its strong hydrophilicity, thereby enhancing the participation of water vapor in the desorption process and further improving the desorption rate of carbon dioxide.
[0023] 2) Silicone to regulate moisture management
[0024] During the absorption process, silica gel, as a hydrophilic material, can promote the gas-solid interface reaction between water vapor and carbon dioxide by maintaining and regulating the moisture on the surface of the absorbent. The introduction of silica gel effectively solves the problem of decreased absorption efficiency of sodium carbonate under low humidity conditions. At the same time, by increasing the formation of surface water film, it enhances the reaction rate during the desorption process and reduces the regeneration energy consumption of the absorbent.
[0025] 3) Magnesium oxide as a catalytic desorption agent
[0026] The adsorbent raw material of the present invention is magnesium chloride, but magnesium chloride becomes magnesium oxide after high-temperature calcination. Magnesium oxide plays a role of catalytic desorption in the adsorbent. Magnesium oxide, due to its good alkalinity and catalytic performance at high temperature, is used as a catalyst in the present invention to significantly reduce the temperature requirement of sodium carbonate in the process of desorbing carbon dioxide. Magnesium oxide can promote the decomposition reaction of sodium bicarbonate at a relatively high temperature and accelerate the release of carbon dioxide. Therefore, the introduction of magnesium oxide is the key to achieving a low-energy consumption, high-speed desorption process.
[0027] 4) The role of porous alumina carrier
[0028] Alumina, as a porous carrier, provides a high specific surface area and more sites for the dispersion and reaction of active components. Its porous structure not only improves the mechanical strength and stability of the absorbent, but also promotes the diffusion of carbon dioxide through the pore network, increasing the absorption and desorption rates.
[0029] 5) Innovative material combination and preparation process
[0030] The present invention innovatively loads a variety of materials (sodium carbonate, potassium carbonate, magnesium chloride, silica gel) into an alumina carrier, optimizes the distribution and pore structure of the materials, and forms an efficient carbon dioxide absorbent. The method performs multiple loadings by impregnation, ensuring the uniform distribution of each component, especially the efficient utilization of trace components, and improving the overall absorption and desorption performance.
[0031] Specific beneficial effects:
[0032] 1) The present invention introduces 5-8% silica gel, 0.5-1% potassium carbonate and 0.3-0.5% magnesium chloride into the sodium-based absorbent to form a mixed-based absorbent. Due to the synergistic effect of sodium carbonate and potassium carbonate, the hygroscopicity and thermal stability of the absorbent are improved, and the absorbent has excellent carbon dioxide absorption capacity.
[0033] 2) The modified absorbent of the present invention can more easily form a stable water film on the surface when it contacts the gas containing water vapor. The presence of this water film accelerates the absorption reaction of carbon dioxide, thereby improving the absorption efficiency.
[0034] 3) The present invention introduces silica gel to adjust the concentration of water vapor during the absorption process, and magnesium chloride is used to catalyze desorption. The absorbent can efficiently desorb carbon dioxide at a relatively low temperature, thereby significantly reducing regeneration energy consumption.
[0035] 4) The porous structure of alumina enhances the mechanical strength and thermal stability of the absorbent, making it suitable for long-term use.
[0036] 5) The optimization of the material of the present invention enables the absorbent to exhibit a faster reaction rate during the absorption and desorption process, which is beneficial to continuous operation and efficiency improvement in the industrial process.
[0037] 6) The improved absorbent of the present invention not only has a higher carbon dioxide selectivity, but also has a lower energy consumption in the regeneration process after absorption, is easy to recycle, and reduces the overall operating cost. DETAILED DESCRIPTION
[0038] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0039] Embodiment 1:
[0040] 1. Pretreatment of alumina carrier and preparation of silica gel solution
[0041] 1.1 Select alumina with high specific surface area (specific surface area greater than 150m 2 / g) as a carrier, weigh 62.6g of alumina particles, use an oven to pre-treat the alumina at a temperature of 120°C to ensure that it is dry; then pre-treat and calcine for 4h (temperature is 500°C) to remove impurities and enhance the pore structure;
[0042] 1.2 Weigh 7.2 g of silica gel powder, pour it into a 50 ml beaker, add 20 ml of deionized water, and stir gently with a stirring rod until it is completely dissolved. This is solution A.
[0043] 2. Use the impregnation method to load the silica gel solution on the alumina carrier and dry and calcine
[0044] 2.1 Take out the pretreated alumina carrier and put it into solution A, making sure it is completely immersed in solution A. Stir it gently with a stirrer for 1 to 2 hours to ensure uniform impregnation.
[0045] 2.2 Use vacuum filtration to remove excess solution from the impregnated alumina;
[0046] 2.3 Place the alumina with excess solution removed in a drying oven and set the temperature between 80 and 120°C for drying for 6 to 12 hours;
[0047] 2.4 Place the dried alumina into a high temperature furnace at a temperature between 400 and 800°C and calcination time of 2 to 4 hours;
[0048] 2.5 The calcined alumina carrier containing silica gel is naturally cooled to room temperature.
[0049] 3. Dissolve sodium carbonate in water to make a solution
[0050] Weigh 36g of sodium carbonate powder, pour it into a 100ml beaker, add 50ml of deionized water, and stir gently with a stirring rod until it is completely dissolved, which is solution B.
[0051] 4. Dissolve potassium carbonate and magnesium chloride in water to make a solution and mix the potassium carbonate solution and magnesium chloride solution
[0052] 4.1 Weigh 1.2g potassium carbonate powder, pour it into a 50ml beaker, add 5ml deionized water, and stir gently with a stirring rod until it is completely dissolved, which is solution C; weigh 0.5g magnesium chloride powder, pour it into a 20ml beaker, add 5ml deionized water, and stir gently with a stirring rod until it is completely dissolved, which is solution D;
[0053] 4.2 Mix solution C and solution D together and stir evenly to ensure that the potassium carbonate and magnesium chloride solutions are fully mixed.
[0054] 5. Use the impregnation method to load the sodium carbonate solution and the mixed solution of potassium carbonate and magnesium chloride on the Al2O3 carrier containing 5-8% silica gel
[0055] 5.1 Place the pretreated alumina carrier containing silica gel into the sodium carbonate solution, ensuring that it is completely immersed in the mixed solution, and gently stir with a stirrer to ensure uniform impregnation. The soaking time is 4 to 5 hours;
[0056] 5.2 Use vacuum filtration to remove excess solution from the impregnated alumina carrier containing 5-8% silica gel;
[0057] 5.3 Place the treated carrier in a mixed solution of potassium carbonate and magnesium chloride for a second impregnation, gently stir with a stirrer to ensure uniform impregnation, the soaking time is 1 to 2 hours, and then use vacuum filtration to remove excess solution from the impregnated material.
[0058] 6. After drying and calcination, a highly efficient sodium-based dry decarbonization absorbent is prepared
[0059] 6.1 Place the dry decarbonization absorbent with excess solution removed in a drying oven and set the temperature to 80-120°C for drying for 6-12 hours;
[0060] 6.2 Place the dried dry decarbonization absorbent into a high temperature furnace at a temperature of 300°C and calcination time of 2 to 4 hours;
[0061] 6.3 The calcined absorbent is naturally cooled to room temperature to obtain the sodium-based dry decarbonization absorbent.
[0062] Embodiment 2:
[0063] The preparation of the high-efficiency sodium-based dry decarbonization absorbent is the same as in Example 1, except that the amount of sodium carbonate added is changed to 24 g and the amount of alumina particles added is changed to 72.6 g.
[0064] Embodiment 3:
[0065] The preparation of the high-efficiency sodium-based dry decarbonization absorbent is the same as in Example 1, except that the amount of sodium carbonate added is changed to 12 g and the amount of alumina particles added is changed to 82.6 g.
[0066] Embodiment 4:
[0067] The preparation of the high-efficiency sodium-based dry decarbonization absorbent is the same as in Example 1, except that the amount of silica gel added is changed to 6 g and the amount of alumina particles added is changed to 63.6 g.
[0068] Embodiment 5:
[0069] The preparation of the high-efficiency sodium-based dry decarbonization absorbent is the same as in Example 1, except that the amount of silica gel added is changed to 8.4 g and the amount of alumina particles added is changed to 61.6 g.
[0070] Embodiment 6:
[0071] The preparation of the high-efficiency sodium-based dry decarbonization absorbent is the same as in Example 1, except that the amount of potassium carbonate added is changed to 0.6 g and the amount of alumina particles added is changed to 63.1 g.
[0072] Embodiment 7:
[0073] The preparation of the high-efficiency sodium-based dry decarbonization absorbent is the same as in Example 1, except that the amount of magnesium chloride added is changed to 0.4 g and the amount of alumina particles added is changed to 62.7 g.
[0074] Embodiment 8:
[0075] The preparation of the high-efficiency sodium-based dry decarbonization absorbent is the same as in Example 1, except that the amount of magnesium chloride added is changed to 0.6 g and the amount of alumina particles added is changed to 62.5 g.
[0076] Comparative Example 1
[0077] A conventional sodium-based absorbent is prepared. The conventional sodium-based absorbent comprises: 30.1% sodium carbonate and 69.9% aluminum oxide.
[0078] The specific operation steps are as follows: (1) dissolving a certain amount of sodium carbonate in deionized water; (2) pouring the alumina carrier into the solution; (3) stirring with a stirrer to ensure uniform impregnation, and the stirring time is 5 to 10 hours; (4) placing in an oven (105°C) for drying; (5) calcining at 300°C in a muffle furnace for 2 hours, and obtaining a traditional sodium-based adsorbent after natural cooling.
[0079] Evaluation of absorption-desorption performance of high-efficiency sodium-based dry decarbonization
[0080] (1) Absorption test
[0081] The absorbent prepared as above was placed in a constant temperature absorption device, and a mixed gas containing 15% carbon dioxide was introduced at 40° C. The absorption rates of the absorbents prepared in Examples 1 to 8 and the absorbent in Comparative Example 1 were tested.
[0082] (2) Desorption experiment
[0083] After absorption saturation, the temperature of the absorbent was raised to 180°C, and an inert gas was introduced to conduct a desorption experiment. At 180°C, the desorption rates of the absorbents prepared in Examples 1 to 8 and the absorbent in Comparative Example 1 were tested.
[0084] The specific evaluation results are shown in Table 1, where the mass ratios of different materials after impregnation in the table are calculated by re-measuring after impregnation and sintering.
[0085] Table 1 Absorption-desorption performance test results of high-efficiency sodium-based dry decarbonization absorbent prepared in Examples 1-8
[0086]
[0087]
[0088] As can be seen from Table 1, the doping of potassium carbonate improves the hygroscopicity of sodium carbonate, enhances the surface ion reaction, and improves the performance of the bicarbonation reaction. When in contact with a gas containing water vapor, it is easier to form a stable water film on the surface. The presence of this water film accelerates the absorption reaction of carbon dioxide, thereby improving the absorption efficiency. The doping of silica gel regulates the surface moisture of the absorbent, promotes the transfer of water vapor during the absorption-desorption process, and increases the desorption rate of carbon dioxide. The doping of magnesium chloride accelerates the desorption process of carbon dioxide under high temperature conditions and reduces the regeneration temperature. When the mass ratio of alumina, silica gel, sodium carbonate, potassium carbonate and magnesium chloride is: 62.6:6:30:1:0.4, the absorption-desorption performance of the absorbent is the best, the absorption rate is increased by 60%, and the desorption rate is increased by 40%.
[0089] The present invention provides a sodium-based dry decarbonization absorbent and a preparation method thereof. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A sodium-based dry decarbonization absorbent, characterized in that: The sodium-based dry decarbonization absorbent is alumina containing silica gel loaded with sodium carbonate, potassium carbonate and magnesium chloride; wherein the sodium-based dry decarbonization absorbent comprises: by mass percentage, 5-8% silica gel, 10-30% sodium carbonate, 0.5-1% potassium carbonate and 0.3-0.5% magnesium chloride, and the rest is alumina.
2. The absorbent according to claim 1, characterized in that The sodium-based dry decarbonization absorbent comprises, by mass percentage, 6% silica gel, 30% sodium carbonate, 1% potassium carbonate and 0.4% magnesium chloride, and the rest is aluminum oxide.
3. The absorbent according to claim 1, characterized in that The water vapor concentration of the sodium-based dry decarbonization absorbent during the absorption process is 0.02-0.04%.
4. A method for preparing a sodium-based dry decarbonization absorbent, characterized in that: The specific steps are: S1. Pretreatment of alumina support; S2. The pretreated alumina support is impregnated in a silica gel solution, and the excess solution is removed, dried, and calcined to obtain an alumina support containing silica gel; S3. The alumina carrier containing silica gel is immersed in a sodium carbonate solution once, and after removing the excess solution, it is immersed in a mixed solution of potassium carbonate and magnesium chloride for a second time. After removing the excess solution, it is dried and calcined to obtain a sodium-based dry decarbonization absorbent.
5. The preparation method according to claim 4, characterized in that: In S1, the pretreatment process is specifically: drying the alumina carrier at 100-150°C, and then calcining at 400-600°C for 3-5h.
6. The preparation method according to claim 4, characterized in that: In S2, the impregnation time in the impregnation process is 1 to 2 hours; the drying process conditions are drying at 80 to 120° C. for 6 to 12 hours; and the calcination process conditions are calcining at 400 to 800° C. for 2 to 4 hours.
7. The preparation method according to claim 4, characterized in that: In S3, the immersion time in the first immersion process is 4 to 5 hours.
8. The preparation method according to claim 4, characterized in that: In S3, the impregnation time in the secondary impregnation process is 1 to 2 hours; the drying process conditions are drying at 80 to 120° C. for 6 to 12 hours; and the calcination process conditions are calcining at 200 to 400° C. for 2 to 4 hours.
9. Use of the absorbent according to any one of claims 1 to 3 in the field of carbon dioxide capture and storage.